Social Sciences Research in Select Four South Asia Countries: A Quantitative Analysis of Publications, 2008-12 - Gupta, Ritu; Tiwari, Rishi; Gupta, B. M. (Journal of Information and Knowledge, 2014)
The overall research output in social sciences consisting of 2681 papers in Pakistan, 993 papers in Bangladesh, 521 papers in Sri Lanka and 331 papers in Nepal during 2008-12 has been analyzed with a view to study the publication growth rate and citation impact, share of international collaborative papers and leading collaborators, broad subject-wise scatter of publications, geographical distribution of publications, contribution and impact of leading institutions and identification of most productive journals contributing to social science research. The data for the study has been derived from Scopus international multidisciplinary bibliographical database.